Extraosseous calcifying epithelial odontogenic tumour. (31st July 2013) - Lanzer, M.; Gander, T.; Grätz, K.; Kruse, A.; Lübbers, H.‐T.
Abstract Calcifying epithelial odontogenic tumour (CEOT) represents a very rare entity of odontogenic tumours. Its subform of an extraosseous CEOT is very rarely seen. In this case report, a patient with an extraosseous CEOT is described, treatment algorithm is reported and literature is reviewed for all cases reported on this kind of tumour.